Pt-Based Oxygen Reduction Reaction Catalysts in Proton Exchange Membrane Fuel Cells: Controllable Preparation and Structural Design of Catalytic Layer - Hongda Li; Hao Zhao; Boran Tao; Guoxiao Xu; Shaonan Gu; Guofu Wang; Haixin Chang (Nanomaterials, 2022)
Proton exchange membrane fuel cells (PEMFCs) have attracted extensive attention because of their high efficiency, environmental friendliness, and lack of noise pollution. However, PEMFCs still face many difficulties in practical application, such as insufficient power density, high cost, and poor durability. The main reason for these difficulties is the slow oxygen reduction reaction (ORR) on the cathode due to the insufficient stability and catalytic activity of the catalyst. Therefore, it is very important to develop advanced platinum (Pt)-based catalysts to realize low Pt loads and long-term operation of membrane electrode assembly (MEA) modules to improve the performance of PEMFC. At present, the research on PEMFC has mainly been focused on two areas: Pt-based catalysts and the structural design of catalytic layers. This review focused on the latest research progress of the controllable preparation of Pt-based ORR catalysts and structural design of catalytic layers in PEMFC. Firstly, the design principle of advanced Pt-based catalysts was introduced. Secondly, the controllable preparation of catalyst structure, morphology, composition and support, and their influence on catalytic activity of ORR and overall performance of PEMFC, were discussed. Thirdly, the effects of optimizing the structure of the catalytic layer (CL) on the performance of MEA were analyzed. Finally, the challenges and prospects of Pt-based catalysts and catalytic layer design were discussed.